2020
DOI: 10.1111/pedi.13131
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management among pre‐teen and adolescent diabetes device users

Abstract: Objective: Despite increased diabetes device use, few adolescents with type 1 diabetes (T1D) meet glycemic targets. We examine associations between utilization of insulin pumps and continuous glucose monitoring (CGM) and glycemic control. Research Design and Methods: This prospective cohort study included 80 youths (10-18 years of age) with T1D. Multiple linear regression and linear mixed models (LMM) were used to estimate the effects of device self-management on HbA1c and daily time in range (70-180 mg/dL), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The theme, “expect the unexpected,” helps to illuminate the youth's experience of daily glucose variability. In Strand et al (2018), youth described the phenomenon of glucose fluctuations as a 'roller coaster', which is consistent with the characterization by youth in our study 13 . This phenomenon of unpredictability is reflected in residual variance analysis from the quantitative portion of this mixed methods study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The theme, “expect the unexpected,” helps to illuminate the youth's experience of daily glucose variability. In Strand et al (2018), youth described the phenomenon of glucose fluctuations as a 'roller coaster', which is consistent with the characterization by youth in our study 13 . This phenomenon of unpredictability is reflected in residual variance analysis from the quantitative portion of this mixed methods study.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, youth's description of self‐management including their characterization of good versus bad days and their frustration over unexpected outcomes were strikingly similar. While youth's described experience was similar, the corresponding quantitative data from phase 1 of this mixed methods study showed frequency of self‐management behaviors (i.e., bolus, SMBG, advanced feature use) varied significantly between youth with high and low A1C 13 . Further exploration of this difference between youth's experience and application of self‐management behaviors is warranted.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We aim to highlight the various roles taken by CDN members, their specific contribution to research, and any limitations identified. We discuss the CDN's role in two particular studies: the first, Mobile-app simulation platform for diabetes self-management, involved usability testing and development of a diabetes education technology, and the second, Self-management among Pre-teen and adolescent INsulin pump users (SPIN), which was a prospective mixed methods observational study examining pre-teen and adolescent diabetes technology selfmanagement (Faulds et al, 2020).…”
Section: Special Issue Articlementioning
confidence: 99%